PENGARUH PERSEDIAAN DAN PIUTANG TERHADAP TINGKAT LIKUIDITAS PADA TOKO ELETRONIK CAHAYA BERSINAR - Sharon Purba, Nico; Diana, Nana (STIE Atma Bhakti, 2024)
The data used is secondary data. The population in the study is all financial statement data andthe sample is financial statement data from 2018 to 2022. Then analyzed using multiple linearregression analysis assisted by the spss 25.0 program. Based on the results of the analysis, theinventoryandaccountsreceivablevariablesdonothaveasignificanteffectonthelevelofliquidityin the Shining Light Electronics Store. The liquidity level at the Shining Light Electronics Storecanbeexplainedbytheinventoryandaccountsreceivablevariablesby84.5%andtheremaining15.5% is explained by other variables. The relationship between the inventory and accountsreceivablevariablesandtheliquidity levelisclassified asvery strongat 91.9%.